Intraperitoneal and periportal injection of bupivacaine for pain after laparoscopic cholecystectomy - Maharjan, SK; Shrestha, S (Kathmandu University Medical Journal, 2009)
Purpose: to study the analgesic efficacy of intraperitoneal and periportal injection of bupivacaine following laparoscopic cholecystectomy. Materials and methods: 40 patients undergoing laparoscopic cholecystectomy were randomized into two groups of 20 each. Group A (study group) received 40 ml of intraperitoneal injection of 0.25% bupivacaine and 20 ml of same concentration in 4 ports, 5 ml each at the end of surgery. Group B (control) received no treatment. Post operative patient monitoring and pain assessment was done by another doctor blinded to the procedure using VAS score at 1,2,3,6,9 and 24 hours after surgery. Pethidine 50 mg intramuscular was given as rescue analgesic when demanded by patient within first 24 hours. Results: when VAS score was analyzed in the two groups, the study group had less scores compared to control group though it was statistically not significant (p > 0.05). The rescue analgesic requirement was significantly less in study group (p < 0.00). Conclusion: Intraperitoneal and periportal injection of bupivacaine is effective in decreasing pain after laparoscopic cholecystectomy. Key words: Laparoscopic surgery, intraperitoneal bupivacaine, analgesia, VAS score doi: 10.3126/kumj.v7i1.1765 Kathmandu University Medical Journal (2009), Vol. 7, No. 1, Issue 25, 50-53